Evaluation of effectiveness parameters on gas dehydration plant - Chen Sing, Winnie Lo (2012)
Dehydration of Natural Gas to controlled water content is necessary in order to avoid gas hydrates and minimize corrosion.This study describes the dehydration on liquid desiccant dehydration unit.The key task was to identify the optimum parameters used in Triethylene Glycol dehydration unit.Absorption dehydration involves the use of Triethylene Glycol to remove water vapor from the gas stream.Water was removed to meet a water dew point requirement of sale gas contract specification range from 32.8 to 117 kg/106 standard m3.The evaluation of effectiveness parameters on gas dehydration plant was carried out by using ASPEN HYSYS simulation.ASPEN HYSYS was used for steady state simulation, design, performance monitoring and optimization of oil and gas production,gas processing and petroleum refining industries.Peng-Robinson equation of state was chosen in the system.The simulation was carried out to determine the effect of important parameters such as column operating pressure, number of theoretical stages of column and gas flow rate.A technically optimized dehydration process has been proposed based on the simulated data.Results showed that, when the gas flow rate increases, the water absorption rate will decrease. Same condition obtained as increasing pressure.However,water absorption rate increases with the increasing number of theoretical stages.The optimum condition of gas dehydration was at 2000kPa with 1000m3/h gas flow rate and 4 column theoretical stages.